Phallogocentrism, Global Entanglements and Comparison in the Study of Religion Mysticism and Gender as Category of Knowledge among Muslim Intellectuals (1938–41) - Maltese, Giovanni (Interdisciplinary Journal for Religion and Transformation in Contemporary Society, 2023)
Along with the critique of generic terms, such as religion or mysticism, regarded as Western-centric, comparison in religious studies has been faulted for reinforcing Western dominance over the rest of the world. Global Religious History claims to constructively address these charges by focusing on global entanglements. On closer inspection, however, if the latter are theorized at all, an astounding exclusion comes to the fore: the omission of gender as category of knowledge. Engaging this phallogocentrism in Global Religious History, this article calls for a conceptualization of global entanglements that takes this omission seriously. As a case study, I use a tract published serially in a Singapore-based Islamic missionary journal (1938–1941), to argue that a revised conceptualization of global entanglements can help to uncover the contributions of non-hegemonic subjects to contemporary discourses on religion, mysticism, Islam, and Sufism, as well as to the comparative study of religion.
CRIS-Team Scopus Importer:2024-03-27
Keywords: 1930s/40s; Gender; Islam; Mysticism; Phallogocentrism; South and Southeast Asia; Sufism